Operation and configuration of reverse electrodialysis for thermal to electric conversion applications. - Hulme, Anna Macklennan (Cranfield University, 2020)
Reverse electrodialysis (RED) is a membrane-based technology which enables the sustainable production of electricity through harnessing the Gibbs free energy of mixing solutions with a salinity gradient. Whilst RED research has largely focussed on power production from sea water and river water, efforts to decarbonise the energy sector have led to interest in ‘closed-loop’ RED, which utilises synthetic saline solutions for applications in energy storage and thermal to electric conversion. To realise the potential of RED for these applications, research is required to determine the operating conditions and configurations which enable high power output and energy efficiency and reduce the levelised cost of electricity. In this work, the use of sodium chloride solutions with an increased concentration gradient in a recycle configuration is demonstrated to maximise the work produced from a fixed volume when current density is optimised, minimising the unitary cost of electricity produced by RED. However, these conditions exacerbate phenomena such as osmosis, ionic transport, and concentration polarisation, introducing complex temporal effects which must be managed. Features of electrodialysis modules such as an increased intermembrane distance and the low water permeability of membranes have been demonstrated to improve energy efficiency obtained using these feeds at low current densities, however, compromises power density at higher current densities. Membranes with low water permeability and low resistance are required to maximise power and energy efficiency using these feeds. Whilst the use of larger stack size has been shown to be associated with greater exergy losses due to water transport, increasing the cell pair number has been identified as an effective strategy to increase the process scale, enabling improvements to both power and efficiency.
Keywords: Closed-loop; reverse electrodialysis heat engine; salinity gradient energy; brine; blue energy; low-grade heat